Nodular hidradenoma mimicking nodular basal cell carcinoma - Elisangela M.A. Lima; Mariana O. Fernandes; Marina Silva; Flávia R. Ferreira; Fernanda G. Moya (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
A 40-year-old woman, phototype III, presented with an erythematous, sessile nodule with small ulceration points on the right forearm for 1 year and 6 months. Dermoscopy showed structures similar to blue-gray globules, arboriform telangiectasias with some thickened vessels, bright white spots, and microulceration points. The main hypothesis of nodular basal cell carcinoma (BCC) and excisional biopsy of the lesion were performed. Histopathology showed nodular adnexal epithelial neoplasia without atypia, with a focal connection to the epidermis, a clear cell component, and immunohistochemistry positivity for p63, epithelial membrane antigen (EMA), and cytokeratin AE1/AE3, concluding the diagnosis of nodular hidradenoma. The unusual presentation, mimicking a nodular BCC, and the importance of the correct approach to atypical lesions motivated this report.